2015
DOI: 10.1080/10548408.2014.962723
|View full text |Cite
|
Sign up to set email alerts
|

Tourists’ Perceptions of London, United Kingdom (UK), as a Safe Host City During the 2012 Olympic Games

Abstract: The Olympic Games 2012 provided the host city London with the opportunity to showcase its cultural diversity and world-class tourist attractions. However, the build-up to the world's largest sporting event attracted considerable negative publicity primarily related to security at the Games, namely terrorism and its potential to disrupt the spectacle. Intercept interviews were carried out with 354 spectators during the Games at public viewing sites and key tourist attractions to elicit the perceptions of London… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…To maximize the return on investments and to minimize criticism and/or skepticism from the public regarding the use of public funding on various costs associated with the events, governments and/or municipalities must find viable ways to justify the funds being spent on the hosting of mega sporting events. As evidenced by previous research (George and Swart, 2015; Kaplanidou, 2006), one possible way to increase benefits that derive from the hosting of mega sporting events would be attracting more tourists before, during, and after the events. Economic impact focuses on economic benefits attributed to an event that would have not occurred otherwise (Brown et al, 2016).…”
Section: Introductionmentioning
confidence: 84%
“…To maximize the return on investments and to minimize criticism and/or skepticism from the public regarding the use of public funding on various costs associated with the events, governments and/or municipalities must find viable ways to justify the funds being spent on the hosting of mega sporting events. As evidenced by previous research (George and Swart, 2015; Kaplanidou, 2006), one possible way to increase benefits that derive from the hosting of mega sporting events would be attracting more tourists before, during, and after the events. Economic impact focuses on economic benefits attributed to an event that would have not occurred otherwise (Brown et al, 2016).…”
Section: Introductionmentioning
confidence: 84%
“…Comparatively little attention has been paid to the behavior of tourists in respect of their perception of safety experienced during a visit to an urban destination. Although few studies found that safety is a choice of a behavioral attribute which influences tourists' "repeat visitation" [92,93], few studies have illustrated the relationship between the perception of safety and tourist satisfaction. The results of this study confirm that a tourist who has a better perception of safety exhibits a higher level of satisfaction and also indicate that a tourist who has a good experience in terms of personal safety with regard to an urban destination would be more willing to provide a positive WOM recommendation.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…From the studies, it is also found an interplay of emotions and risk perceptions in attendee responses to the threat of terrorism. Aside from notable exceptions (i.e., Cleland & Cashmore, 2018; George & Swart, 2015), similar research has failed to reappear, despite claims that terrorism concerns have affected attendance on sporting events. In their sociological study of fan responses to “security,” “surveillance,” and “risk,” Cleland and Cashmore (2018) make findings suggesting that match-goers expect, desire, and accept additional security at professional sports events.…”
Section: Literature Review: Spectators’ Responses To “Safety” and “Sementioning
confidence: 99%